Factors affecting hospitalisation costs per admission for cervical cancer patients - Noriza Majid; Hng, Chong Khen; Chew, Kah Teik; Azimatun Noor Aizuddin (Penerbit Universiti Kebangsaan Malaysia, 2024)
Cervical cancer ranks among the top ten most prevalent cancers in Malaysia, and it is the second most common cancer in women. A lot of money has been said to be spent on treating cervical cancer. That's why the community and health care professionals need to know how much it will cost to treat this cancer. The purpose of this study is to estimate the average cost of cervical cancer treatment and to determine the factors that influence this cost. From 2013 to 2022, 829 cervical cancer patient samples were collected by the International Casemix and Clinical Coding Centre (ITCC), Hospital Canselor Tuanku Muhriz (HCTM). Among the information gathered includes the treatment cost for one episode of care, the patient's age, clinical factors such as the length of their hospital stay, presence of additional medical issues, cancer severity level, kind of metastasis, type of treatment, and the patient's discharge status. Regression analysis was employed in this investigation. The skewed structure of the treatment cost data is taken into account by including a logarithmic adjustment, which transforms the model for treatment cost estimation. The results demonstrate that the cost of treatments is affected by a number of factors. These factors include the severity of the cancer, the length of hospital stay, the presence of kidney failure or brain metastases, and the type of treatment (surgery, etc.). Decreases in treatment expenses are observed in patients who are older, who have heart disease or bone metastases, who have undergone radiation treatment, and who are homebound upon discharge.